2007
DOI: 10.1002/ijc.23018
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RANTES and MCP‐1 in epithelial cells is regulated via LMP1 and CD40

Abstract: Epstein-Barr virus (EBV)-associated undifferentiated nasopharyngeal carcinoma (NPC) is characterized by a prominent nonneoplastic lymphoid stroma. The functional role of these inflammatory cells and the mechanism of their recruitment are not fully understood. In B-cells, the EBV-encoded latent membrane protein 1 (LMP1) can induce the expression of chemokines in an NF-jB dependent manner. We now show that LMP1 can induce the expression of RANTES and MCP-1 in an epithelial cell line, and that this effect is part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…thase (iNOS) in vitro. [19][20][21][22][23] Interestingly, the levels of IL-8, IL-12, RANTES and MCP-1 are increased in the BAL of LTR with BOS 24,25 and the expression of iNOS is elevated. 26 Possibly, EBV contributes to the development of BOS by inducing the production of these cytokines.…”
Section: Discussionmentioning
confidence: 96%
“…thase (iNOS) in vitro. [19][20][21][22][23] Interestingly, the levels of IL-8, IL-12, RANTES and MCP-1 are increased in the BAL of LTR with BOS 24,25 and the expression of iNOS is elevated. 26 Possibly, EBV contributes to the development of BOS by inducing the production of these cytokines.…”
Section: Discussionmentioning
confidence: 96%
“…Production of lymphotactic cytokines has been hypothesized to be a strategy used by EBV to recruit additional lymphocyte targets during infection to enhance the establishment of a persistent infection (51). Indeed, EBV LMP-1, which was detected at all time points studied during EBV-2 T-cell infection, has been shown to upregulate production of IL-8, RANTES, and MIP-1␣ (52)(53)(54)(55). Whether LMP-1 is directly responsible for the high levels of these cytokines observed in EBV-2-infected T-cell cultures and how expression of the cytokines affects the infectious process in vivo have yet to be determined.…”
Section: The Cd8mentioning
confidence: 99%
“…Expression of several chemokines has been demonstrated in NPC tumors, including IL-8, macrophage inflammatory proteins (MIPs), macrophage chemoattractant proteins (MCPs), and RANTES (11,70,75). Considering that EBV may promote chemokine production in B lymphocytes (49), an issue is raised as to how EBV infection of the epithelial tumor cells contributes to the production of chemokines and the recruitment of leukocytes in NPC.…”
mentioning
confidence: 99%
“…Previous studies have focused on the effects of EBV latent infection and revealed that viral latent membrane protein 1 (LMP1) is a chemokine inducer. LMP1 can upregulate IL-8, RANTES, and MCP-1 in epithelial cells, mainly through a NF-B-mediated mechanism (11,22,75). Since LMP1 pro-tein is not always detected in NPC biopsies (23,76), it is worth examining whether other EBV gene products may be also involved in the regulation of chemokines.…”
mentioning
confidence: 99%